ZnO Nanorods Grown Directly on Copper Foil Substrate as a Binder-Free Anode for High Performance Lithium-Ion Batteries - Huang, Lanyan; Wang, Xin; Yin, Fuxing; Zhang, Yongguang; Gao, Jinwei; Liu, Junming; Zhou, Guofu; Bakenov, Zhumabay (International Journal of ELECTROCHEMICAL SCIENCE. www.electrochemsci.org, 2016)
ZnO nanorods directly grown on copper foil substrate were obtained via hydrothermal method without using templates. Structure and morphology of the as-prepared ZnO nanorods were characterized by X-ray diffraction, scanning electron microscopy and high-resolution transmission electron microscopy. The ZnO nanorods on copper foil (ZnO@CF) exhibited remarkably enhanced performance as anode for lithium batteries with the initial discharge capacity of 1236 mAh g-1 and a capacity of 402 mAh g-1 retained over 100 cycles at a current density of 200 mA g-1. The ZnO@CF anode demonstrated an excellent rate capability, delivering a reversible capacity of 390 mAh g-1 at 1500 mA g-1. This superior performance of the ZnO@CF anode is believed to be due to the unique structure of this binder-free anode, favoring mass and charge transfer at its interface with the electrolyte, effectively reducing the Li-ions diffusion paths and providing conditions to accommodate the anode volume variations upon charge-discharge cycling.
Keywords: Lithium ion battery; Anode; ZnO nanorods; Binder-free; Research Subject Categories::NATURAL SCIENCES::Chemistry::Analytical chemistry::Electrochemistry